Pengaruh Perkembangan Karier Dan Kepuasan Kerja Terhadap Komitmen Organisasi - Resia Priskila; Mei Ie (Jurnal Manajerial Dan Kewirausahaan, 2021)
Senior High School (SMA) institution is an educational institution that is required to bring out graduates so they can join public universities (PTN) and become prime human resources. So school educational institutions need human resources such as school principals and teachers as organizational wheels to drive activities. To achieve these goals, the school is required to pay attention to the work commitment of the teachers by paying attention to career development variables and job satisfaction, this is based on career development that runs in an organization that can increase their commitment to the organization in achieving organizational goals because the teachers have job satisfaction with the existing job promotion system so as to improve work quality. The purpose of this study was to determine the effect of career development and job satisfaction on organizational commitment in a highschool in Jakarta teachers. Researchers distributed questionnaires to all teachers who teach at a highschool in Jakarta, totaling 55 respondents to be the sample for the entire study. The data analysis method in this research is quantitative method using Structural Equation Modeling (SEM), through the Partial Least Square approach. The results of this study show that career development affects organizational commitment to teachers of a highschool in Jakarta and job satisfaction affects organizational commitment of a highschool in Jakarta teachers. Lembaga institusi Sekolah Menengah Atas (SMA) merupakan lembaga pendidikan yang dituntut untuk menghasilkan lulusan yang unggul agar dapat masuk PTN dan menjadi sumber daya manusia yang unggul. Oleh karena itu, institusi lembaga pendidikan sekolah memerlukan sumber daya manusia sebagai penggerak roda kegiatan seperti kepala sekolah dan guru dalam roda organisasi. Dalam mencapai tujuan tersebut pihak sekolah dituntut untuk memperhatikan komitmen kerja bapak/ibu guru dengan memperhatikan variabel pengembangan karir dan kepuasan kerja. Hal tersebut didasarkan atas pengembangan karir yang berjalan dalam sebuah organisasi dapat meningkatkan komitmen mereka terhadap organisasi dalam mencapai tujuan organisasi karena karyawan bapak/ibu guru memiliki kepuasan kerja dengan adanya sistem promosi jabatan yang ada sehingga meningkatkan kualitas kerja. Tujuan penelitian ini adalah untuk mengetahui pengaruh pengembangan karir dan kepuasan kerja terhadap komitmen organisasi pada Guru di sebuah SMA di Jakarta. Peneliti menyebarkan kuesioner kepada seluruh bapak/ibu guru yang mengajar di sebuah SMA di Jakarta yang berjumlah 55 responden. Metode analisa data dalam penelitian ini yaitu metode kuantitatif dengan menggunakan Structural Equation Modeling (SEM), melalui pendekatan Partial Least Square, Hasil penelitian ini menunjukkan pengembangan karir berpengaruh terhadap komitmen organisasi pada guru di sebuah SMA di Jakarta dan kepuasan kerja berpengaruh terhadap komitmen organisasi pada guru di sebuah SMA di Jakarta.